2014
DOI: 10.1080/02640414.2014.928827
|View full text |Cite
|
Sign up to set email alerts
|

Motivational patterns as an instrument for predicting success in promising young football players

Abstract: 20Psychological characteristics are crucial to identifying talents, which is why these are being 21 incorporated in today's multidimensional talent models. In addition to multidimensionality,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 32 publications
7
79
0
Order By: Relevance
“…Often, the complex interplay of physiological, psychological and socioeconomic factors is not considered or quantified in many TI and TD processes even when it is generally accepted that certain psychological traits are characteristics found in a highly successful athlete 9. Abbott and Collins10 called for a continual monitoring system that accounts for psychobehavioural dispositions when identifying potential talent and its efficacy, which was documented in a group of Swiss youth footballers where those who reported a high level of intrinsic-achievement-orientation were more likely to be gain membership in the national team 11…”
Section: Talent Identification and Talent Development Of Sport In Youmentioning
confidence: 99%
“…Often, the complex interplay of physiological, psychological and socioeconomic factors is not considered or quantified in many TI and TD processes even when it is generally accepted that certain psychological traits are characteristics found in a highly successful athlete 9. Abbott and Collins10 called for a continual monitoring system that accounts for psychobehavioural dispositions when identifying potential talent and its efficacy, which was documented in a group of Swiss youth footballers where those who reported a high level of intrinsic-achievement-orientation were more likely to be gain membership in the national team 11…”
Section: Talent Identification and Talent Development Of Sport In Youmentioning
confidence: 99%
“…Motivation is one of the driving forces underlying athletes’ effort expenditure and dedication to their sport . Athlete motivation can be nurtured by a wide variety of factors, including the true enjoyment and challenge of an activity but also more external rewards such as money, contingent regard from others, and media attention.…”
Section: Introductionmentioning
confidence: 99%
“…Motivation is one of the driving forces underlying athletes' effort expenditure and dedication to their sport. 1,2 Athlete motivation can be nurtured by a wide variety of factors, including the true enjoyment and challenge of an activity but also more external rewards such as money, contingent regard from others, and media attention. Self-Determination Theory [3][4][5] presents different forms of motivation on a continuum of increasing self-determination, with intrinsic motivation representing the hallmark of volitional or autonomous functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, extrinsic motivation has been split into four different levels: external regulation, introjected regulation, identified regulation and integrated regulation. Conceptual links between the self-determination theory and the achievement goal theory have been observed in several studies (Chin, et al, 2012;Ntoumanis, 2001;Zuber et al, 2015) demonstrating that task oriented individuals are more self-determined and more intrinsically motivated, whereas ego oriented individuals are less self-determined and more extrinsically motivated (Ntoumanis, 2001). Through an extensive quantitative review, found a significant and small to moderate relationship in meaningfulness between the task goal orientation and amotivation (r w =-.13), extrinsic motivation (r w =.20), external regulations (r w =.12), internal regulations (r w =.34) and intrinsic motivation (r w =.47).…”
Section: Introductionmentioning
confidence: 94%
“…Self-determination theory (Deci & Ryan, 1985) and the achievement goal theory (Nicholls, 1989) are two of the most common theoretical approaches to studying achievement motivation in sport and physical activity (Fenton, Duda, & Barrett, 2016;Zuber, Zibung, & Conzelmann, 2015).…”
Section: Introductionmentioning
confidence: 99%